IMPACT OF ANTHROPMETRIC MEASURES ON SURAL NERVE CONDUCTION IN HEALTHY SUBJECTS - Saeed, S.; Akram, M. (Journal of Ayub Medical College Abbottabad, 2008)
Background: Nerve conduction studies are an invaluable aid to investigate and quantify the physiological activity of peripheral nerves. These include measurement of sensory and motor conduction velocities and latencies of peripheral nerves. These nerve conduction parameters may be affected by anthropometric factors like age, sex, height, weight and BMI. In this observational study the impact of these anthropometric parameters was measured on sensory nerve conduction velocity (SNCV) and sensory latency (SNSL) of sural nerve. Method: Sural nerve conduction studies were conducted in EMG room of Neurology section of Medical Unit 1 at Sir Ganga Ram Hospital, Lahore on Electromyograph by Nihon Kohden MEB-5304K. Results: After following strict exclusion criteria by careful history and physical examination 25 normal healthy subjects recruited from local population by random sampling technique. The age range was 40-70 years with mean age 47.2±9.23 years. Gender distribution was 60% females and 40% males. The mean SNCV was found to be 53.16±5.68 meter per second (m/sec) and mean SNSL was 2.81±0.45 milliseconds (msec). Conclusion: It was found that the mean sural nerve conduction velocity was higher and the mean sensory latency was shorter in healthy subjects than that of the Western races. Moreover, the SNCV decreases and SNSL increases significantly with age. Key words: Nerve conduction studies, sensory nerve conduction velocity (SNCV), sensory latency, Sural nerve.